Assessment of Indonesian-Language Orthodontics-Related YouTube Video as a Source of Information - Hariyani, Ninuk; Rahmawati, Aurellia; Rachmawati, Yuanita Lely; Rahardjo, Anton; Maharani, Diah Ayu (European Journal of Dentistry, 2022)
Objectives Health-seeking behavior through social media including orthodontics treatment has become popular among community in Indonesia. However, the characteristics of uploaded video in term of quality, reliability, and usefulness are unknown. This study aims to analyze the characteristics of Indonesian-language orthodontic-related YouTube videos uploaded.Materials and Methods This study adopted cross-sectional design and analyzed 300 videos as the sample. A final 100 related videos were included for analysis of the quality, usefulness, and reliability of the video uploaded as well as viewers' interaction in term of popularity and visibility. Mann–Whitney's test was used for the statistical analysis.Results The majority of the videos were uploaded by individual users (60%) with moderate quality, usefulness, and reliability. Statistical analysis showed that orthodontics-related YouTube videos uploaded by individuals have lower popularity and reliability compared with health professional (p < 0.05).Conclusion Most of the Indonesian-language orthodontic-related YouTube videos have moderate quality, usefulness, and reliability. There is a need from health professional to contribute more related video as main source of health information for the general to make healthy health-seeking behavior.
Keywords: Indonesia; orthodontics; videos; YouTube; internet